Os filhos do destino: a exposição e os expostos na freguesia Madre de Deus de Porto Alegre (1772-1837) - Silva, Jonathan Fachini da (Universidade do Vale do Rio dos Sinos, 2014)
This study intends to further contribute with the historical knowledge of a phenomenon widely accepted and practiced during the Ancient Regime. The exposure of children in the Parish Madre de Deus de Porto Alegre, between 1772 and 1837, is a subject that has not received much approach by the southern historiography. It is important to highlight that, during this period the Parish Madre de Deus did not have a Santa Casa de Misericórdia with an active foundling wheel to help this children, which, in this context, were left on the doorstep of this population, a common fact in other regions of Brazil as well. In the absence of the foundling wheel, the Portuguese legislation and the Imperial legislation that succeed it left the responsibility to care and raise those rejected children to the Municipal Chamber, which had to pay wet nurses and baby sitters or, as it happened in the case studied here, the Chamber would pay wages to the families willing to raise those children. In this sense, another issue that has been analyzed was the action of Porto Alegre's Municipal Chamber regarding those children throughout the proposed period, as caring for them was the Chamber's responsibility. After we rebuild this administrative setting of foundling children, we will analyze the demographical dimension of this phenomenon, verifying not only the profile and the conditions of the foundling itself, but also trying to detect and study the traits of the "receiving" households, as well as take notice of the (exposed) subject in that society. To achieve the objectives proposed here, we use a set of sources, explored by crossing the information contained in the Termos de Vereanças, produced by the Municipal Chamber, and in the parochial records (baptism, marriage and death), as well as crossing these with other ecclesiastic sources, such as confessants lists, wills and matrimonial habilitations. The main theoretical-methodological approaches adopted in this study are those from Historical Demography, which offers us adequate methods of analysis, as well as a historiographic foundation regarding this subject in Social History, Family History and History of Children.
Keywords: Expostos; Câmara; Freguesia Madre de Deus de Porto Alegre; Foundling; City councill; Parish Madre de Deus de Porto Alegre; ACCNPQ::Ciências Humanas::História